Հայաստանի Հանրապետության պարսկալեզու վիմագիր ժառանգությունը - Միքայելյան, Տիգրան (ՀՀ ԳԱԱ Արևելագիտության ինստիտուտ)
The conquest of Armenia by the Muslim rulers was often accompanied with encouraged infiltration of Arabs and later Kurds, Persians, and mostly Turkic-speaking nomadic tribes especially after the mass deportation of the Armenians to Iran by Shah Abbas in 1604 and the following years. The Muslim rulers and their ordinary subjects residing in Armenia have left their traces in the forms of various epigraphic inscriptions (constructional, memorial mostly as tombstones). Among the Arabic-lettered inscriptions of the 9-19 cc. (the absolute majority of which are tombstones traditionally written in Arabic) some have also been carved in the Persian language.
Keywords: Պարսկական վիմագրություն